Quality test of IPIP-NEO personality instrument items for indonesian sample (Develop short version 90-items for indonesian sample) - Ali, Abdurosid Nur; Akhtar, Hanif; Winarsunu, Tulus; Silfiasari, Silfiasari; Widyasari, Dian Caesaria (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Increasing popularity of personality research on facet level, followed by instrument developments such as IPIP-NEO, that freely usable and modifiable measures. Research using the IPIP-NEO instrument is often conducted in Indonesia.Purpose: This study aims to analyze the quality of items and develop a short version of the IPIP-NEO-300 for Indonesian samples that measures thirty facets within Big Five personality domains. The processes undertaken in this study include item analysis using the Rasch Model, the development of a shorter scale, and validation of this shortened version.Method: The total subjects in this research is 759 people with an age range of 11-46 years. The sampling technique used for subject selection is convenience sampling, and data collection was carried out online using google forms.Findings: These results indicate that IPIP-NEO 300 and IPIP-NEO 90 are psychometrically acceptable and practically convenient for measuring Big Five Personality on the facet level. IPIP-NEO short version 90 has a high correlation with IPIP-NEO 300, which means that IPIP-NEO short version can be used to measure personality in Indonesian samples.Implication: The results of this study can enrich the psychometric literature in Indonesia and provide a basis for more specific and contextual personality research.